Development of power generation system using piezoelectric and electromagnetic induction techniques on lab-on-a-disc (LOD) for localized heating / Karunan Joseph - Karunan, Joseph (2017)
This thesis presents the development of a power generator on the Lab-on-a-Disc (LOD) for biomedical applications using two energy harvesting techniques. The first power generator was developed using piezoelectric films and the second power generator was developed using electromagnetic induction technique. The rotational environment during the operation of the disc was used by the power generators to harvest electrical energy using piezoelectric films and electromagnetic induction technique. For the first power generator, 6 pieces of piezoelectric film (thin film PVDF) are embedded on the disc with a small circular magnet at the end of each film to resemble a cantilever system. A permanent magnet was installed on the stationary base, close to the outer edge of the disc. As the power generator disc rotates, the small magnet attached at the outer end of the piezoelectric film will be attracted to the permanent magnet and bends the film. This mechanism induces mechanical vibration to the piezoelectric film and generates electrical power. The second power generator disc is embedded with 6 stacks of copper coils placed over a set of N52 neodymium permanent magnets. The permanent magnets provide strong magnetic field over the power generator disc and as the disc rotates, the copper coils cuts the magnetic field and current will be induced in the copper coil stacks. The piezoelectric film based generator was able to produce 24 microWatt at 83.775 rad/s (800RPM) while the electromagnetic induction based power generator produced 125 miliWatt at 157.08 rad/s (1500RPM). Based on the power generation characteristic of each technique, the best power generator was used to demonstrate a localized heating system on the disc. Localized heating technique can be used to perform on-disc incubations and thermal cycling for numerous biomedical applications. Due to ability to produce higher electrical power, the localized heating system was embedded with the electromagnetic induction based power generator. The system reported to achieve up to 58.62°Celsius at spinning speed of 230.38 rad/s (2200RPM).